Hybrid perovskite exchange of PbS quantum dots for fast and high-detectivity visible–near-infrared photodetectors. Issue 23 (13th May 2020) - Mi, Longfei; Chang, Yajing; Zhang, Yan; Xu, Enze; Jiang, Yang
Abstract : A hybrid perovskite decorated with PbS-QDs by using a ligand exchange process to fabricate high-performance photodetectors. Abstract : PbS quantum dots (QDs) were regarded as promising candidates for photoelectric devices because of their high absorption, multiple exciton generation effect and solution processability. However, their low charge carrier transport behavior impedes their wide application. Here, a ligand exchange process was introduced to fabricate PbS-QD + hybrid perovskite photodetectors. The photodetectors show a high sensitivity, low noise current and high stability under visible to near-infrared light illumination. The devices exhibited an impressive responsivity of ∼2 × 10 6 A W −1 and a high photoconductive gain of ∼3 × 10 6, respectively, with an applied bias of 5 V. Furthermore, the photodetectors display a large detectivity approaching 10 15 Jones and a fast photoresponse up to 1 MHz at room temperature. These great performances suggest that the hybrid perovskite can well passivate the defects of PbS-QDs and provide new insight into the preparation of high-performance nano-devices.